Homem idoso: vivência de papéis durante o ciclo vital da família - Santos, Ivanilza Etelvina dos (2006)
The more the number of the elderly people, in Brazil and in the world increase, the more important is the achievement of the study and the research in this field which carry out effective ways of intervention which can contribute to drive the human and socials sciences professionals in the attendancing and the setting of services and programs which have got this population as their main objective. The present work comes down to a research carried out in Paulo Afonso City, Bahia interland, with six male elderly who take part in the Third Age Project (Third Age Open University) as well as the community six elderly. The general purpose was to look over their perception about the roles experienced along the vital cycle of the family. Individual appointments were achieved, which were transcribed and analysed by topics. The study shows the strictness from the old men s role in our culture, which begins with the son, uncle, brother, husband, home supporter and grandfather. These old people came from traditional families in which the roles were strict and hierarchicals, without an opening for dialogues among one another. The son had no active voice in the family while the father was the supporter, emotionally far and without setting any affectionate relationship with wife or children. This behaviour is clearly presented along from the interviewers reports. These old people have been reproducing the same family dynamics in their general relationship, as they use to do with their own family. In both groups, the hierarchy was clearly presented. The difference is set up in the perspective and future plans between the Reviver Project old people and the community one. As the first ones show themselves more optimistcs, the community one show some bigger convenience as well as some lack of perspective. We can also realize some contraditions between the two groups: both groups asserted that beforetime they were more respected and beloved, despite of the few laws protecting them; although, they told that nowadays they have been respected by the young and that they shouldn t cry out against the family and the social relationship as well. We hope that this work may be a contribution to the ones who are interested in the old people affairs as well as to the ones who deal with families affairs